DISCOURSE ANALYSIS OF REPUBLISHED HOAX - Agus Ari Iswara; Kadek Yogi Susana; Ni Made Lisma Martarini (Haluan Sastra Budaya, 2023)
One of the way of hoaxes spreads is that old hoax narratives are republished then can be redistributed, so that we encounter them more and more often. This study examined the transformation pattern of repeated hoax narratives. The data were qualitative, collected using library and triangulation methods. The data was collected from the Turnbackhoax.id. Data documentation used the 'Search' menu. Keywords used to get pre-transformation and post-transformation hoaxes. To optimize the search, it was done by inputting the title in full, in part, or only relevant keywords. The analysis was carried out using the side-by-side comparison method assisted by the Plagiarism Checker application. The analysis also applied the triangulation method with journalistic theories. The data presented were pre-modified and post-modified. Data was presented in an organized and periodic manner from old hoaxes to recycled hoaxes. The analysis was presented descriptively. The results indicated two things. First, old hoaxes that were republished could be categorized into hoaxes with fixed and transformed narratives. Each of these categories had a different movement. Second, narrative transformation in recycled hoaxes could be in the form of paraphrasing, minimal changes, addition, reduction and elimination, unique (different), alphabetic transformation, and transformation of nominal or numeric values.